Answer:
(y-6)/6 = x
Step-by-step explanation:
y+4x=10x-6
Subtract 4x from each side
y+4x-4x=10x-4x-6
y = 6x-6
Add 6 to each side
y +6 = 6x-6+6
y+6 = 6x
Divide by 6
(y-6)/6 = 6x/6
(y-6)/6 = x
Answer:
7z^3+6z^2-27z+22
Step-by-step explanation:
The given question is of subtraction:
So,
(7z^3+42z^2-15z+1)- (36z^2+12z-21)
=7z^3+42z^2-15z+1-36z^2-12z+21
Combining alike terms to simplify
=7z^3+42z^2-36z^2-15z-12z+1+21
=7z^3+6z^2-27z+22
So the answer in simplified form is:
7z^3+6z^2-27z+22 ..
Answer:
It is C. Just look at the farthest points, and those are the numbers in your inequality.
B, 2 5/8.
2 and 5/8 times itself is 5 1/4, meaning its half of 5 1/4.